Method of Automatic Generation of Questions and Answers for Knowledge Testing Systems - S. А. Migalevich; Ju. O. German; O. V. German (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2025)
The technique of automatic generation of questions and answers for knowledge testing is considered. The proposed approach is based on the developed method of defining and using clusters of keywords to generate questions and answers based on a global or local language model, which constitutes theoretical and applied novelty. Clusters are built on the basis of a corpus of text documents related to the studied area (textbooks, methodological manuals, electronic resources). The technical solution presented in the article is logically complete and can serve as a basis for practical developments.